Prasugrel Intermediate Metabolite Modulates Platelet Inhibition by Negatively Interfering With an Active Metabolite: An Ex Vivo, In Vitro, and In Silico Study - Minuz, Pietro; Giorgetti, Alejandro; Meneguzzi, Alessandra; Taus, Francesco; Ribeiro, Rui P; Baldessari, Filippo; Gargiulo, Giuseppe; Gragnano, Felice; Landi, Antonio; Castelli, Marco; Gottardo, Rossella; Bortolotti, Federica; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2025)
Prasugrel is converted into prasugrel active metabolite (PAM; R-138727) through the cytochrome P450-mediated conversion of an intermediate metabolite (PIM; R-95913). It is unknown whether PIM exerts any biological function. The FABOLUS-FASTER trial (Facilitation Through Aggrastat or Cangrelor Bolus and Infusion Over Prasugrel: A Multicenter Randomized Open-Label Trial in Patients With ST-Elevation Myocardial Infarction Referred for Primary Percutaneous Intervention) showed that chewed prasugrel does not improve bioactivity, in spite of accelerated PAM kinetics. PIM and PAM pharmacokinetics were assessed by mass spectrometry in blood samples collected from ST-segment-elevation myocardial infarction patients randomized to chewed (n=17) or integral (n=15) 60 mg prasugrel. The ex vivo and in vitro effects of PAM and PIM were assessed on ADP-induced platelet activation. The binding sites of PIM and PAM were investigated by molecular dynamics simulation. Chewed prasugrel was associated with higher PIM levels compared with integral prasugrel: PIM median area under the curve (25-75 p): 73 (41.5-92.0) versus 33 (0.0-50.0) ng·h/mL ( <0.05). PIM plasma concentrations negatively correlated with inhibition of ADP-induced platelet aggregation, which strongly correlated to the PAM/PIM ratio (ρ=0.782; <0.001; n=30) than PAM, suggesting an antagonistic role of PIM on PAM-induced P2Y inhibition. Subsequent in vitro tests confirmed the dose-dependent, reversible antagonistic effect of PIM on PAM inhibition of aggregation (maximum effect, -49.5% [95% CI, -54.4% to -44.6%]; <0.001), confirmed by P-selectin expression and vasodilator-stimulated phosphoprotein phosphorylation as readouts at the signaling level. At molecular dynamics simulations of the drug-receptor systems, PIM accommodates through noncovalent reversible binding in the same PAM-binding site, distinct from that of 2-methylthio-adenosine-5'-diphosphate. PIM negatively interferes with PAM, thereby reducing its inhibitory activity, likely competing at the P2Y receptor-binding site. URL: https://www.clinicaltrials.gov; Unique identifier: NCT02978040. URL: https://www.clinicaltrialsregister.eu; Unique identifier: EudraCT 2017-001065-24.